Morphological changes in the fast vs slow fiber profiles of the urethras of diabetic pregnant rats - Marini, Gabriela [UNESP]; Barbosa, Angélica M. Pascon [UNESP]; Damasceno, Débora Cristina [UNESP]; Matheus, Selma Maria Michelin [UNESP]; Castro, Rodrigo de Aquino; Girão, Manoel João B. Castello; Rudge, Marilza Vieira Cunha [UNESP] (PAGEPress Publications, 2011)
Background: This study was undertaken to test the hypothesis that diabetes and pregnancy detrimentally affect the normal function of urethral striated muscles in rats, providing a model for additional studies related to urinary incontinence. The aim of this study was to evaluate morphological alterations in the urethral striated muscles of diabetic pregnant rats. Materials and Methods: Twenty female Wistar rats were distributed into four experimental groups of five rats as follows: virgin, pregnant, diabetic virgin, and diabetic pregnant. Diabetes was induced using streptozotocin administration (40 mg/kg i.v.). The rats were lethally anesthetized, and the urethra and vagina were extracted as a unit. Cryostat sections (6 μm thick) were cut and stained with hematoxylin-eosin, and immunohistochemical procedures were performed and subjected to morphological and semi quantitative analysis. Results: The urethral striated muscle from the diabetic pregnant rats presented with the following variations: thinning and atrophy, disorganization and disruption associated with the colocalization of fast and slow fibers and a steady decrease in the proportion of fast vs slow fibers. Conclusion: Diabetes and pregnancy impair the urethral striated muscle and alter its fiber type distribution. © Copyright G. Marini et al., 2011.
Keywords: Diabetes; Pregnancy; Striated muscle fiber; Urethra